The ‘Fascinating’ World of the Evil Eye Beware the Evil Eye: The Evil Eye in the Bible and the Ancient World. Volume 1: Introduction, Mesopotamia, and Egypt, John H. Elliott, James Clarke & Co., 2016 (ISBN 978-0-227-17568-2), xxii + 209 pp., pb £16 Beware the Evil Eye: The Evil Eye in the Bible and the Ancient World. Volume 2: Greece and Rome, John H. Elliott, James Clarke & Co., 2016 (ISBN 978-0-227-17613-9), xxxvi + 334 pp., pb £27.50 Beware the Evil Eye: The Evil Eye in the Bible and the Ancient World. Volume 3: The Bible and Related Sources, John H. Elliott, James Clarke & Co., 2017 (ISBN 978-0-227-17667-2), xxx + 354 pp., pb £32 Beware the Evil Eye: The Evil Eye in the Bible and the Ancient World. Volume 4: Postbiblical Israel and Early Christianity through Late Antiquity, John H. Elliott, Wipf and Stock, 2017 (ISBN 978-1-4982-3072-8), xxvi + 220 pp., pb 29 - Askin, Lindsey A. (Reviews in religion and theology, 2019)
The Evil Eye is a pervasive folkloric belief in the eye as an active organ. Historically, the belief and its related protective practices have been much maligned by modern Western attitudes. Origins of the belief, as best as can be traced, are pinned to ancient Mesopotamia and Egypt. From there, the belief radiated outwards until it was pervasive throughout the ancient Near East and Mediterranean world including, as Elliott argues, ancient Judaism and early Christianity. Conceptualizations of the Evil Eye and related beliefs and protective practices have been found as far as Brazil, Tibet, and Australia and are still expressed in Western society. Elliott's four-volume work on the Evil Eye in antiquity is a contextual reception history that draws together both textual sources and material culture of this fascinating belief across the ancient world.